Creating a New Narrative: A theory of how adopted individuals readjust their adoptive identity in parenthood. (October 2022) - Egan, Mary; O'Connor, Anne B; Egan, Jonathan
There is limited research into the experiences of adopted individuals in adulthood despite the fact that adoption is a lifelong process. One key element of adoption is the processing and integration of one's adoptive identity. This becomes increasingly salient in adulthood and especially so when becoming a parent as it leads to a re-examination of the individual's adoptive narrative. However, this phenomenon is not well researched and lacks a theoretical framework. This study employed a classic grounded theory (CGT) methodology to develop a theory that explains how adopted individuals readjust their adoptive identity when they become parents. Twelve interviews were conducted with adoptees who had become parents and analysed using CGT. From this data, the theory of Creating a New Narrative emerged to chart the process and explain how adopted individuals readjust their adoptive identity in parenthood. It involves parents revisiting their adoption narrative and being empowered to reclaim their identity, rescript their family concept and parenting values and expand their repertoire for navigating hypervigilance regarding rejection. All of these elements are influenced by the level of openness and acceptance parents have experienced in relation to their adoptive status. The model thus provides a new theoretical framework that integrates the various research findings in this area.